Additive advantage in characteristics of MIMCAPs on flexible silicon (100) fabric with release‐first process. Issue 2 (20th November 2013) - Ghoneim, Mohamed T.; Rojas, Jhonathan P.; Hussain, Aftab M.; Hussain, Muhammad M.
Abstract We report the inherent increase in capacitance per unit planar area of state‐of‐the art high‐κ integrated metal/insulator/metal capacitors (MIMCAPs) fabricated on flexible silicon fabric with release‐first process. We methodically study and show that our approach to transform bulk silicon (100) into a flexible fabric adds an inherent advantage of enabling higher integration density dynamic random access memory (DRAM) on the same chip area. Our approach is to release an ultra‐thin silicon (100) fabric (25 µm thick) from the bulk silicon wafer, then build MIMCAPs using sputtered aluminium electrodes and successive atomic layer depositions (ALD) without break‐ing the vacuum of a high‐κ aluminium oxide sandwiched between two tantalum nitride layers. This result shows that we can obtain flexible electronics on silicon without sacrificing the high density integration aspects and also utilize the non‐planar geometry associated with fabrication process to obtain a higher integration density compared to bulk silicon integration due to an increased normalized capacitance per unit planar area. (© 2014 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)